Banking Crises and Crisis Dating : Theory and Evidence - Loukoianova, Elena (IMF Working Papers; Working Paper ;, 2009)
Many empirical studies of banking crises have employed "banking crisis" (BC) indicators constructedusing primarily information on government actions undertaken in response to bank distress. Weformulate a simple theoretical model of a banking industry which we use to identify and constructtheory-based measures of systemic bank shocks (SBS). Using both country-level and firm-level samples, we show that SBS indicators consistently predict BC indicators based on four major BCseries that have appeared in the literature. Therefore, BC indicatorsactually measure lagged government responses to systemic bank shocks, rather than the occurrence of crises per se. We re-examine the separate impact of macroeconomic factors, bank market structure, deposit insurance, andexternal shocks on the probability of a systemic bank shocks and on the probability of governmentresponses to bank distress. The impact of these variables on the likelihood of a government responseto bank distress is totally different from that on the likelihood of a systemic bank shock.Disentangling the effects of systemic bank shocks and government responses turns out to be crucial inunderstanding the roots of bank fragility. Many findings of a large empirical literature need to be re-assessed and/or re-interpreted.